Tricho-rhino-phalangeal syndrome: a rare case of disharmonious short stature - Selenia Lorenza Curatola (Accademia Peloritana dei Pericolanti, 2021)
Tricho-rhino-phalangeal syndrome (TRPS) is a genetic disease characterized by craniofacial and skeletal malformations including short stature, brachydactyly, with ulnar or radial deviation of the fingers, clinodactyly and early joint dysplasia, especially of the hips. The most remarkable craniofacial features are slow growing, sparse and brittle hair, pear-shaped nose with a bulbous tip, flat philtrum with thin upper lip, micrognatia and large low-set ears. The radiological hallmarks include cone-shaped phalangeal epiphyses, typical of all TRPS patients, but usually not present until 2 years of age, while bone exostoses appear only in TRPS II individuals. Management is primarily supportive. We describe a case of a male child with disharmonious short stature, affected by TRPS I. The diagnosis was established on the basis of clinical features and genetic testing